ChemInform Abstract: Csp2—N Bond Formation via Ligand‐Free Pd‐Catalyzed Oxidative Coupling Reaction of N‐Tosylhydrazones and Indole Derivatives. Issue 5 (4th February 2014) - Roche, Maxime; Frison, Gilles; Brion, Jean‐Daniel; Provot, Olivier; Hamze, Abdallah; Alami, Mouad
Abstract The new method for the synthesis of substituted N‐vinylazoles shows a broad functional group tolerance.